$CH_2CIF$ Adsorbed on $TiO_2$: Study of the Adsorbate-Substrate Interaction by IR Spectroscopy and DFT Calculations (Journal of Atomic and Molecular Sciences, 2010)
Fourier-transform infrared spectroscopy has been used for the first time to study the adsorption of chlorofluoromethane ($CH_2ClF$)  on $TiO_2$ at room temperature. The obtained spectra allow to deduce that the adsorbate-substrate interaction occurs through both the $Cl$ and $F$ atoms of the molecule and the surface Lewis acid site $(Ti^{4+}$) and by means $H$-bonds involving the $CH_2$ group and the surface Lewis basic sites ($O^{2-}$ or OH$^-$). In order to better comprehend these interactions, a periodic quantum-mechanical study at DFT/B3LYP level has been carried out by considering the anatase (101) surface and focusing the attention on the determination of the energetically possible adsorbate-substrate structures. According to the comparison between the experimental and calculated vibrational frequencies, it can be concluded that the molecule can adsorb on the surface both through the $Cl$ atom and an $H$-bond and by means the $F$ atom and two $H$-bonds.